Penatalaksanaan Fisioterapi Pada Kasus Carpal Tunnel Syndrome Di Rumah Sakit Dr. Moewardi Surakarta - Prianto, Benidektus Adi, Dwi Rosella K, S.St FT., M.Fis (2015)
Background :Carpal tunnel syndrome is one of the most common diseases of the median nerve, which is a entrapment neuropathy on wrist. With disorders such us pain, numbness, and tingling at nervus madianus innervation area. Aims of Research : To study about physiotherapy management in reducing pain, increasing muscle strength, increasing range of motion and functional activities in the case of carpal tunnel syndrome using modalities Ultra Sound (US) and neurodynamic technique. Results: After six times therapy, the obtained results for static pain is T0 : 4 to T6 : 2, motion pain T0 : 6 to T6 : 2, press pain T0 : 6 to T6 : 2, increasing range of motion T0 S: 60o-0o-50o to T6 S: 70o-0o-75o and T0 F : 20o-0o-30o, to T6 F: 20o-0o-35o. increasing muscle strenght flexor wristT0 : 4 to T6 : 5,ekstensor wristT0 : 4 to T6 : 5,radial deviasi T0 : 5 to T6 : 5, ulnar deviasiT0 : 5 to T6 : 5, indeks katzT0 : independence for 5 rating, to T6 : indepedence for 6 rating. Conclusion : Ultra Sound (US) and neurodynamic techniques can reducing pain, increasing muscle strength, increasing range of motion and functional activities of CTS (carpal tunnel syndrome) problems. Keyword : Carpal tunnel syndrome(CTS),entrapment neuropathy,nervus medianus, neurodynamis,ultra Sound (US), upper limb tension test (ULTT), paresthesia.